PELAKSANAAN BANTUAN SOSIAL NON TUNAI DI KELURAHAN DELIMA KECAMATAN TAMPAN KOTA PEKANBARU TAHUN 2018 - Alisma "; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The implementation of social assistance on a non-cash basis has begun in 2017, the purpose of the implementation of social assistance is to reduce the burden of household expenditure through meeting some of the basic food needs in the form of rice and eggs, with the amount of aid disbursed as much as Rp. 110,000 for each recipient the benefits. Social assistance has an implementation mechanism that is, the process of legalization and opening an account, the implementation of education and outreach, the process of channeling, withdrawing money or purchasing goods. The implementation of social assistance is carried out according to the mechanism in Presidential Regulation No. 63 of 2017 which has been determined and carried out according to the procedure.Based on the data that the writer found, the formulation of the problem in this study is why the implementation of non-cash social assistance in Delima Village, Tampan District, Pekanbaru City in 2018 is not optimal due to lack of two-way communication between the manager and the recipient of aid and the disposition of the implementor who does not carry out responsibility answered in accordance with the provisions, the purpose of the study was to find out the implementation of non-cash social assistance in the Delima Village Tampan District Pekanbaru City in 2018 and to find out what factors influence the implementation of non-cash social assistance in the Delima Village Tampan District Pekanbaru City 2018.The concept of the theory I use is the theory of policy implementation. Broadly speaking, the implementation of the policy where the policy making stage between the formation of policies and the consequences of policies for the people affected, to find out how to implement good policies. This research uses qualitative approach with descriptive methods.The results of the study of the implementation of non-cash social assistance in Delima were not optimal due to the lack of two-way communication between the manager and the recipient where the communication was in the form of lack of socialization given by the sub-district facilitator to the beneficiary where the socialization provided was not carried out every month, but only in certain months. And the disposition or character of the implementor is not good enough in carrying out the task so that the disbursement of aid is not timely. Keywords : implementation, non-cash social assistance, implementation of public policies